Insights into the multifunctional applications of strategically Co doped MoS2 nanoflakes. Issue 23 (24th October 2022) - Rahman, R.; Chaudhuri, S.; Samanta, D.; Pathak, A.; Nath, T. K.
Abstract : Simultaneous tuning of magnetic, transport and electrochemical properties through strategic doping of cobalt (Co) ions in hydrothermally treated multi-layered MoS2 nanoflakes (NFs). Abstract : Simultaneous tuning of magnetic, transport and electrochemical properties through strategic doping of cobalt (Co) ions in hydrothermally treated multi-layered MoS2 nanoflakes (NFs) without having a secondary phase has been regarded as cutting-edge research. In our study, we have successfully incorporated Co into MoS2 NFs at various percentages (0%, 2%, 4%, 6%, 8%) with a significant presence of defects, strain and sulfur vacancies, enabling prompt transformation of the surrounding 2H-MoS2 local lattice into a trigonal (1T-MoS2 ) phase. Effective amplification of magnetic property (ferromagnetic coupling on the scale of p eff ∼ 4.37 μ B ) in 8% Co-doped MoS2 NFs has been evidenced from VSM measurements. The key reasons are probably attributed to the doping induced 1T phase, the presence of zigzag edges well-established from TEM and Raman measurements, and exchange interactions between ferromagnetically ordered sulfur vacancies and Mo 4+ and Co 2+ ions. The experimental observations on magnetic measurements have been fitted well with the well-known density-functional theory (DFT) computation. Further, the effect of intentional doping on transport property has been evaluated by employing a four probe linear geometry setup. The increased carrier concentration and decreased resistance result in improved transport properties. Various transport models such as variable range hopping (VRH) and nearest neighbour hopping (NNH) of the Co-doped MoS2 systems have been successfully fitted in different temperature regimes with a tunable temperature coefficient of resistance (TCR) ∼ 3.0 × 10 −2 K −1 . Additionally, electrochemical measurements revealed a significant increase in electrochemical activity with the highest proportion of Co doping (8% Co), which is likely due to increased defect levels and active surface area with expanded interlayer separation, as well as exposure of the electrochemically more active metallic (1T phase) Mo atoms in the edge planes. Therefore, our approach in achieving mixed-phase defect-rich (1T and 2H) Co-doped MoS2 NFs exhibiting room-temperature ferromagnetism, high TCR and improved electrochemical performance makes them an excellent multifunctional candidate in spintronics, infrared (IR) detection and energy storage devices.